SEMIOTIKA PESAN DAKWAH DALAM LIRIK LAGU “IBU” KARYA HAJI IWAN FALS: STUDI DALAM PERSEPSI MAHASISWA IAI AL-AZIS - syarifudin, Ali; Sulistyani, Anjar; maulana, imang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research discusses the importance of understanding how students, as educated young generations, interpret the da'wah messages hidden in song lyrics. This study aims to analyze the da'wah messages contained in the lyrics of Haji Iwan Fals' song